Investment trend on millennials and fintech fraud mitigation - Tifa Noer Amelia; Andi Gazly Satrya Amal (Global Business & Finance Review (GBFR), 2024)
Purpose: This study analyzed the effect of financial literacy, social media, risk perception, and investment willingness on millennials in Jakarta, Indonesia quantitatively. This paper also discusses fraud mitigation qualitatively about the investment trend among millennials. Design/methodology/approach: This type of research is a mixed method between a quantitative approach to see the investment trend, and a qualitative approach to see how to mitigate fraud in the use of fintech. The population in this study are millennials residing in Jakarta with social media accounts and interest in investment in conventional and Sharia capital markets, and how fintech fraud can be anticipated. Findings: This research proves that in the different research groups but the same demography, the independent variable (financial literacy, social media exposure, and risk perception) simultaneously has an influence on millennials' Intention to invest, but does not partially affect it. Fraud in fintech can be prevented through technology, education, and regulation that are continuously reviewed and improved to provide higher relevancy. Research limitations/implications: This research is limited to the investment trend and fintech fraud mitigation on millennials in Jakarta, the capital city of Indonesia. Future research requires a wider age range and demographic of respondents. Originality/value: Investment trends among millennials have a high potential for fraud. To prevent fraud, the association, regulator, and society must be aware of the fraud practice, and technological advancement, evaluating continuously the rewards and punishments of the fintech service.
Keywords: 650; Financial Literacy; Social Media Exposure; Risk Perception; Intention to Invest; Fraud Mitigation